The Use of Comparative Language Styles in the Podcast Agak Laen Official Episode Vanessa Zee Rela Cuti Demi Kejar Impian - Febri Ola Hutauruk; Evelina Harefa; Alpiani Lubis; Andreas Alessandro Hutagalung; Halimatussakdiah (Tradition and Modernity of Humanity, 2026)
This study aims to identify and analyze the forms of comparative language style used in Vanessa Zee's YouTube episode of the Agak Laen Official podcast. Comparative language style is a figure of speech used to compare one object with another to create a more engaging and understandable communication effect. This study employed a qualitative approach with descriptive methods and content analysis. Data were collected through library research by quoting words and sentences containing comparative language style from podcast video transcripts. The data analysis technique refers to the Miles and Huberman model, which includes three stages: data reduction, data presentation, and conclusion drawing/verification. The results show various forms of comparative language style used by the speakers in the podcast to express ideas, experiences, and emotions in a more lively and engaging manner, thereby enhancing the communication appeal of the podcast content.